2009
DOI: 10.1073/pnas.0908268106
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-4 conducts proper elastogenesis via interaction with cross-linking enzyme lysyl oxidase

Abstract: Great arteries, as well as lungs and skin, contain elastic fibers as important components to maintain their physiological functions. Although recent studies have revealed that a glycoprotein fibulin-4 (FBLN4) is indispensable for the assembly of mature elastic fibers, it remains to be elucidated how FBLN4 takes part in elastogenesis. Here, we report a dose-dependent requirement for FBLN4 in the development of the elastic fibers in arteries, and a specific role of FBLN4 in recruiting the elastin-cross-linking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 48 publications
7
144
0
1
Order By: Relevance
“…10). The severe elastic fibre phenotype of fibulin-4-depleted mice might thus reflect not only perturbed elastin crosslinking (Horiguchi et al, 2009), but also altered release of LLC from microfibrils. One N-terminal fibrillin-1 Marfan mutant exhibited significantly reduced LTBP-1 binding to fibrillin-1; this binding might also contribute to this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). The severe elastic fibre phenotype of fibulin-4-depleted mice might thus reflect not only perturbed elastin crosslinking (Horiguchi et al, 2009), but also altered release of LLC from microfibrils. One N-terminal fibrillin-1 Marfan mutant exhibited significantly reduced LTBP-1 binding to fibrillin-1; this binding might also contribute to this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of microfibrils in TGF regulation is highlighted by pathologically elevated TGF activity in the connective-tissue disorder Marfan syndrome, which is caused by fibrillin-1 mutations that disrupt the formation and/or stability of tissues such as blood vessels, eyes and bones (Robinson et al, 2006). Mice depleted of fibulin-4, a microfibril-associated molecule, have elastic fibre defects (McLaughlin et al, 2006;Hanada et al, 2007;Horiguchi et al, 2009) and exhibit enhanced aortic TGF activity (Hanada et al, 2007). By contrast, mice lacking microfibril-associated glycoprotein MAGP-1 (also known as MFAP-2) have reduced TGF activity but no overt microfibril defects (Weinbaum et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…88 Interestingly, FBLN4 is also involved in recruiting lysyl oxidase to the elastic fiber, and lysyl oxidase is known to inhibit TGF-β enzymatically. 90 The gene responsible for the arterial tortuosity syndrome (OMIM 208050) is SLC2A10, 61 which codes for glucose transporter 10, a member of the facilitative glucose transporter family (Table 1). Although it is still unclear what the substrate for this transporter is, a link to TGF-β signaling has been suggested (Figure).…”
Section: Disorders Related To Mfs and Ldsmentioning
confidence: 99%
“…In general, the formation of elastic fiber requires various elements, including fibrillin, which provides a scaffold, lysyl oxidase, which mediates the cross-linking reaction of several components including elastin, and DANCE protein as an organizer for elastogenesis. 23,24 Because of the complexity of the components necessary for the formation of elastic fiber, there is still controversy about which additive agents or methods work best for its regeneration. 25 On the other hand, Takahashi et al 26 have reported that the regeneration of normal vascular wall can be achieved in the pulmonary artery using a structure of reinforcing materials without either cell seeding or inductive differentiating factors.…”
Section: Histological Changesmentioning
confidence: 99%